(untitled) (Eurasian Journal of Ecology, 2018)
Soil micromycetes are present in all biocenoses, they are an important part of detrital chains and perform a number of key functions in ecosystems: participation in processes of decomposition of organic matter and nutrient cycling, in soil formation processes, and regulation of the species structure and functional activity of other soil organisms. Despite the ecological significance of soil micromycetes, they remain an insufficiently studied group of organisms. The aim of this work was to study the quantitative composition of micromycete complexes in soils of agrocenoses. The main areas of research are the determination of the number of filamentous fungi and yeasts in soils of agrocenoses of grain and forage crops, the comparative analysis of the number of micromycetes in uncultivated (virgin) soils and cultivated soils of agrocenoses, the identification of the features and patterns of mycobiota distribution in soils under crops. Scientific and practical significance of the work. Information has been obtained on the quantitative composition and distribution of micromycetes in virgin soil and in soils of agrocenoses of 7 grain and forage crops: soybean, barley, lucerne, rape, safflower, sweet clover and sainfoin. Methodology of the study. Isolation of micromycetes from soil samples was carried out soil dilution plating technique on elective nutrient media. Quantitative counting was carried out by counting the grown colonies, followed by recalculation of 1 g soil. Main results. The content of filamentous fungi in soils under agricultural crops varied in the range from (324.3±12.2)×103 to (647.5±22.3)×103 CFU/g of soil, in virgin soil their number did not exceed (312.4±11.3)×103 CFU/g soil. The number of yeast in cultivated soils was in the range from (64.6±2.1)×103 to (212.4±6.5)×103 CFU/g soil., A greater content of mycobiota was found in soils under agricultural crops in comparison with uncultivated soil. The prevalence of micromycetes in the soil of the upper layers (0-10 cm) and the decrease in their number with the deepening into the soil have been established. The vegetation type had a negligible effect on the quantitative composition of micromycetes. The maximum number of fungi was characteristic for soils under soybean, alfalfa and sainfoin; the greatest amount of yeasts is found in soil samples of alfalfa agrocenosis. The abundance of fungi and the smaller content of yeasts in all the investigated variants are shown. The value of the study. The work contributes to the study of the prevalence of soil micromycetes. The volume of accumulated information on the distribution of micromycetes in soils in Kazakhstan at the moment remains insufficient, which determines the value of the studies and obtained results about the abundance and distribution of filamentous fungi and yeasts in uncultivated soil and agrocenosis soils of the agro-industrial firm «Turgen». Practical significance of the results of the work. A collection of saprophytic soil micromycetes has been collected. Key words: micromycetes, number, soil, agrocenosis.